METHODOLOGICAL ASPECTS OF PREPARING FUTURE SPECIALISTS IN PRIMARY MATHEMATICS EDUCATION FOR ORGANIZING LEARNING AND COGNITIVE ACTIVITIES IN THE CONTEXT OF DISTANCE LEARNING - Dolynyuk , Myroslava Myronivna; Shuper , Tetiana Mykolayivna (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2025)
The article examines the methodological approaches to preparing future primary school teachers for the effective organization of educational and cognitive activities in mathematics using distance learning. This article outlines a phased system for developing the professional competencies of prospective educators, aimed at ensuring their readiness to teach effectively in blended or fully online educational settings. The article presents typical problem-based scenarios designed for future specialists in primary mathematics education, that promote the development of critical thinking skills and the ability to make prompt decisions during online learning interactions.